2001
DOI: 10.1359/jbmr.2001.16.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training over 2 Years Increases Bone Mass in Calcium-Replete Postmenopausal Women

Abstract: Understanding the stress/strain relationship between exercise and bone is critical to understanding the potential benefit of exercise in preventing postmenopausal bone loss. This study examined the effect of a 2-year exercise intervention and calcium supplementation (600 mg) on bone mineral density (BMD) in 126 postmenopausal women (mean age, 60 ؎ 5 years). Assignment was by block randomization to one of three groups: strength (S), fitness (F), or nonexercise control (C). The two exercise groups completed thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
112
1
13

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(131 citation statements)
references
References 23 publications
5
112
1
13
Order By: Relevance
“…Among these studies, a few use the strength training, trying to increase the BMD in individuals submitted to that type of physical activity (7,13,14,17) . In general, the same studies have shown positive results related to the BMD (8,15,(17)(18)(19)(20)(21)(22)(23) . Nevertheless, despite this possible benefic effect, quite large training volumes may cause a damage on the BMD, and it seems that such damage is closely related to the disturbance in the hormonal homeostasis of the organism (5,6,24) .…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Among these studies, a few use the strength training, trying to increase the BMD in individuals submitted to that type of physical activity (7,13,14,17) . In general, the same studies have shown positive results related to the BMD (8,15,(17)(18)(19)(20)(21)(22)(23) . Nevertheless, despite this possible benefic effect, quite large training volumes may cause a damage on the BMD, and it seems that such damage is closely related to the disturbance in the hormonal homeostasis of the organism (5,6,24) .…”
mentioning
confidence: 85%
“…In fact, higher training intensities related to the peak load are generally associated to higher stimuli to the increasing BMD than lower intensities (3,13,17,18,22,35) . Besides, the use of higher training intensities implies in more immediate responses on the BMD (3) .…”
Section: Strength Training and Bmdmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Finally, it has been reported that a significant effect of RT in postmenopausal women (mean age, 60 +/-5 years) over 2 years at the clinically important intertrochanter hip site (+1.1%). 46 Remarkably, the maximum change in BMD occurred in the first year of the intervention. There was lative decline in the rate of change during the second year; however, BMD remained more than a 3% difference between the exercise and control group after 2 years.…”
Section: Effects Of Resistance Training On Bone Massmentioning
confidence: 94%
“…Nevertheless, RT is still one of the most recurrent types of exercise applied in order to improve bone mass in elderly individuals; especially in preventing bone loss among postmenopausal women. 21,46 Previous studies have reported that RT is able to prevent bone demineralization in older women. 47,48 For instance, the study by de Matos, et al 48 reported that 12 weeks of weight training, among postmenopausal women with osteoporosis or osteopenia, did not significantly improve BMD (1.17%) at the lumbar spine in the exercise group (n=30).…”
Section: Effects Of Resistance Training On Bone Massmentioning
confidence: 99%